2017
DOI: 10.1002/bdd.2080
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization and tissue expression of marmoset cytochrome P450 2E1

Abstract: Common marmosets (Callithrix jacchus) have attracted increasing attention as a useful small non-human primate model in preclinical research. However, studies on marmoset cytochrome P450 (P450) 2E enzyme have scarcely been conducted. In this study, the full-length cDNA encoding P450 2E1 enzyme was isolated from marmoset livers by reverse transcription (RT)-polymerase chain reaction (PCR). Marmoset P450 2E1 amino acid sequences were highly identical (>88%) to those of cynomolgus monkey and human P450 2E1 enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Recombinant human and marmoset P450 2D6 enzymes effectively catalyzed R -metoprolol O -demethylation, consistent with the activities of human and marmoset hepatic microsomes (Table 2 ). Investigations of typical human P450 2E1 substrates showed that hepatic microsomes from humans, cynomolgus monkeys, and marmosets catalyzed p -nitrophenol 2-hydroxylation, chlorzoxazone 6-hydroxylation, and theophylline 8-hydroxylation at similar rates [26]. Recombinant human, cynomolgus monkey, and marmoset P450 2E1 catalyzed these drug oxidation reactions, suggesting that P450 2E1 plays a similar role in drug-related oxidation reactions in human and marmoset livers (Table 2 ).…”
Section: Drug Oxidation Activities Mediated By Marmoset Hepatic Micromentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant human and marmoset P450 2D6 enzymes effectively catalyzed R -metoprolol O -demethylation, consistent with the activities of human and marmoset hepatic microsomes (Table 2 ). Investigations of typical human P450 2E1 substrates showed that hepatic microsomes from humans, cynomolgus monkeys, and marmosets catalyzed p -nitrophenol 2-hydroxylation, chlorzoxazone 6-hydroxylation, and theophylline 8-hydroxylation at similar rates [26]. Recombinant human, cynomolgus monkey, and marmoset P450 2E1 catalyzed these drug oxidation reactions, suggesting that P450 2E1 plays a similar role in drug-related oxidation reactions in human and marmoset livers (Table 2 ).…”
Section: Drug Oxidation Activities Mediated By Marmoset Hepatic Micromentioning
confidence: 99%
“…Numbers in parentheses are the positions of drug oxidations. The substrate concentrations were: ethoxyresorufin (2.0 µM) [22], 7-ethoxycoumarin (20 µM) [30], coumarin (100 µM), pentoxyresorufin (10 µM) [30], propofol (20 µM) [30], efavirenz (20 µM) [30], paclitaxel (100 µM) [12], tolbutamide (100 µM) [12], flurbiprofen (20 µM) [12], diclofenac (10 µM for 4′-hydroxylation and 100 µM for 5-hydroxylation) [12], R/S -warfarin (10 µM) [41], R/S -omeprazole (10 µM) [12], bufuralol (20 µM) [24], R/S -metoprolol (10 µM) [27], chlorzoxazone (50 µM) [26], p -nitrophenol (50 µM) [26], theophylline (500 µM) [26], midazolam (20 µM) [24], nifedipine (50 µM) [24], testosterone (100 µM) [24], progesterone (100 µM) [24], terfenadine (2.0 µM) [23], and ebastine (20 µM) [19].…”
Section: Fig (1)mentioning
confidence: 99%
See 1 more Smart Citation